2020
DOI: 10.1152/ajpregu.00201.2020
|View full text |Cite
|
Sign up to set email alerts
|

NTS and VTA oxytocin reduces food motivation and food seeking

Abstract: Oxytocin (OT) is a neuropeptide whose central receptor-mediated actions include reducing food intake. One mechanism of its behavioral action is the amplification of the feeding inhibitory effects of gastrointestinal (GI) satiation signals processed by hindbrain neurons. OT treatment also reduces carbohydrate intake in humans and rodents and correspondingly, deficits in central OT receptor (OT-R) signaling increase sucrose self-administration. This suggests that additional processes contribute to central OT eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 74 publications
2
25
1
Order By: Relevance
“…In addition to oxytocin acting in the NTS to amplify vagally-mediated satiation signals, Wald and colleagues revealed that NTS oxytocin signaling reduces conditioned motivated behaviors for palatable food. Specifically, oxytocin administration to the NTS reduces motivation to work for sucrose in a progressive ratio schedule of operant reinforcement, and reduces reinstatement of palatable food-seeking behavior [ 47 ]. Altogether, these data indicate that NTS OT-R signaling is important for amplification of GI signals in the control of both satiation and food-motivated behavior.…”
Section: Neural Sites Of Action For Oxytocin’s Effects On Food Intakementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to oxytocin acting in the NTS to amplify vagally-mediated satiation signals, Wald and colleagues revealed that NTS oxytocin signaling reduces conditioned motivated behaviors for palatable food. Specifically, oxytocin administration to the NTS reduces motivation to work for sucrose in a progressive ratio schedule of operant reinforcement, and reduces reinstatement of palatable food-seeking behavior [ 47 ]. Altogether, these data indicate that NTS OT-R signaling is important for amplification of GI signals in the control of both satiation and food-motivated behavior.…”
Section: Neural Sites Of Action For Oxytocin’s Effects On Food Intakementioning
confidence: 99%
“…Further, numerous studies have shown that central oxytocin preferentially reduces intake of and motivated responding for sweet-tasting palatable foods, in part, through actions on the VTA and ACB [ 7 , 10 , 64 , 67 , 68 ]. For example, recent evidence demonstrates that direct administration of an OT-R antagonist in the VTA significantly increases sucrose intake [ 10 ], and VTA OT-R agonism reduces sucrose motivation and chocolate pellet seeking [ 47 ]. A potential molecular mechanism through which oxytocin exerts these effects may be through modulation of dopaminergic signaling.…”
Section: Neural Sites Of Action For Oxytocin’s Effects On Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Has their feeding gained a compulsive nature that is insensitive to satiety signals? These questions can be answered with operant tasks, where rodents receive food contingent on their actions (Curtis et al, 2019;Mourra et al, 2020;O'Connor et al, 2015;Skinner, 1938;Thorndike, 1898;Wald et al, 2020). Typically, operant behavior is tested in dedicated chambers for a few hours each day.…”
Section: Introductionmentioning
confidence: 99%
“…4h The supraoptic nucleus (SON) responds to acute LiCl 43,44 . It is the primary site of oxytocin production, which is known to have emetic and anorectic properties [45][46][47][48] . The c-Fos response in the SON increased markedly in response to LiCl [F (2,16) =54.36, p< 0.001 effect of treatment], with no response to Boost® (Fig.…”
Section: C-fos Immunoreactivity During Cta Acquisition and Expressionmentioning
confidence: 99%